The Effect of Professional Skepticism and Information Technology onAuditors Performance - Andi Kusumawati; Asrini; Arifuddin; Asri Usman (www.amertainstitute.com, 2023)
The purpose of this article is to analyze the influence of professional skepticism and information technology on auditors' performance. This study is a type of quantitative study. Population in this study is BPK South Sulawesirepresentative auditors with 103 auditors as a sample by sample method saturated. The types of data in this studyare the primary data use questionnaires in collecting the data with 64 returning respondents. Deep data analysis techniques study This using the regression model selection test , the assumption test classical , multiple linear regression , and hypothesis testing Partial with SPSS version 25 . Based on the results of data analysis, the findingsof this study are professional skepticism and information technology has a positive and significant effect on auditor performance.